2002
DOI: 10.1136/gut.51.5.628
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog expression correlates with fundic gland differentiation in the adult gastrointestinal tract

Abstract: Background: Sonic hedgehog (Shh) is an important endodermal morphogenetic signal during the development of the vertebrate gut. It controls gastrointestinal patterning in general, and gastric gland formation in particular. We have previously shown that Shh regulates gastric gland proliferation in the adult but detailed analysis of its expression along the adult gastrointestinal tract has never been undertaken. We therefore studied Shh expression along the normal human and rodent adult gastrointestinal tract as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
117
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 33 publications
7
117
2
1
Order By: Relevance
“…2,4 Studies have shown that Hh signalling from the epithelium is required for the correct specification and patterning of the underlying mesenchyme. [5][6][7] In the adult human colon, expression of Shh mRNA has been demonstrated in a few epithelial cells at the base of normal intestinal crypts, 8 suggesting a role for SHH in the maintenance of the stem cell compartment. Further evidence of a role for Hh signalling in intestinal epithelial cell proliferation comes from targeted disruption of Ihh in the mouse.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,4 Studies have shown that Hh signalling from the epithelium is required for the correct specification and patterning of the underlying mesenchyme. [5][6][7] In the adult human colon, expression of Shh mRNA has been demonstrated in a few epithelial cells at the base of normal intestinal crypts, 8 suggesting a role for SHH in the maintenance of the stem cell compartment. Further evidence of a role for Hh signalling in intestinal epithelial cell proliferation comes from targeted disruption of Ihh in the mouse.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] A study in the adult human gut showed expression of SHH primarily in the fundic glands of the stomach. 8 Shh mRNA was detected in a small number of epithelial cells at the base of the crypts of the small and large intestine. 8 Secreted SHH and IHH signal through binding to the PTCH receptor, which, in the absence of ligand, represses the activity of the transmembrane protein SMO.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Also in the human adult intestine, Shh expression is restricted to the region corresponding to stem cells (van den Brink et al, 2002;de Santa Barbara et al, 2003) and upregulated in the neoplastic or inflammatory intestine when the stem cells compensate for the epithelial damage (Berman et al, 2003;Nielsen et al, 2004). Therefore, it seems likely that the stem cells may make their niche adequate for the new epithelial formation by expressing Shh, which in turn ) and Chordin proteins to the medium changes the proliferating activity of intestinal tissues cultured for 5 days.…”
Section: Bmp-4 Activity Is Regulated By Th-induced Shh and Chordinmentioning
confidence: 99%